(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article analyzes the significance of using leguminous products like mung beans and beans in treating patients with digestive system disorders. Mung beans and beans are rich in numerous beneficial nutrients that improve digestive health, normalize intestinal activity, and help reduce inflammation. The article highlights the effectiveness of mung beans and beans in dietary therapy for digestive diseases based on scientific studies and statistical data. Additionally, the article discusses the positive and negative effects of incorporating these products into the diet, along with practical recommendations for their preparation and consumption.